Strategi Pengembangan Wisata Bahari Desa Namu Guna Mendukung Perekonomian Masyarakat Sadar Wisata - Palupi, Ratna Diyah; Ira, -; Risfandi, - (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2019)
The consequence of tourist village is the community's psychology and environmental carrying capacity. Good strategy will be able to realize the welfare of the village community. The purpose of this study is to make a tourism development strategy in the Namu Village. Methods of data collection using sampling techniques through interviews and questionnaires with a total samples of 70 respondents. Characteristics of tourism conditions and potential are analyzed by supply-demand. While demand analysis is used to recognize the pattern of visitor demand. Both of these analyzes are used as reference materials for development strategies by strengths, weaknesses, opportunities, and threats SWOT analyzed. Furthermore, based on the Internal Factor Analysis Summary (IFAS), the beauty of Namu and the waterfall become the main attraction for tourist destination. On the other side the disadvantage is the unpreparedness of the Namu village community make them not enough in economically. External Factor Analysis Summary (EFAS), partisanship of the government enable for Namu to be developing in marine tourism. However the threats was come from outside investor which can reduce the role of the community to improve their economy. Based on the analysis of IFAS and EFAS, the Namu Village's tourism development strategy is to improve the quality of tourism objects, increasing the role of the government, looking for investors especially in the transportation sector, improve community capacity. For instance manufacture of fishery products, souvenirs, and culinary. Finally safeguard ecosystems through waste management